Treatment by serum up-conversion nanoparticles in the fluoride matrix changes the mechanism of cell death and the elasticity of the membrane. (November 2016) - Pleskova, Svetlana N.; Gorshkova, Ekaterina N.; Novikov, Viktor V.; Solioz, Marc
Highlights: Up-conversion nanoparticles caused neutrophils died by necrosis and mummification. Protein coating up-conversion nanoparticles reduce their toxicity. Neutrophils died by necrosis significantly decrease of membrane rigidity. Neutrophils died by mummification significantly increase of membrane rigidity. Abstract: Nanoparticles are increasingly being used for treatment and diagnostic purposes, but their effects on cells is not fully understood. Here, the interaction of fluorescent up-conversion nanoparticles (UpC-NPs) with neutrophils was investigated by imaging and measurement of membrane-cytosceletal elasticity by atomic force microscopy. It was found that UpC-NPs induce the death of neutrophils mainly by necrosis, and to a smaller extent by a novel process called 'mummification'. Necrosis occurs by gradual loss of intracellular contents and nuclei, 45–110 min after exposure to UpC-NPs. Mummification is apparent as an increase in the rigidity of the neutrophils' membrane and acquisition of a characteristic bumpy shape with numerous protrusions; this structure does not change during atomic force microscopy scanning. Coating UpC-NPs with protein by incubation with serum leads to (1) formation of nanoparticle aggregates in the nm and μm size range, (2) a reduction in toxicity, (3) reduced mummification of neutrophils, and (4) no significant reduction of the elasticity of the membrane-cytoskeletal complex of neutrophils 30 min after exposure to coated UpC-NPs. The study shows that serum proteins greatly curb the toxicity of nanoparticles and reveals mummification as a novel mechanism of UpC-NP-induced cell death.